Study on RPKI Safeguard Based on Local Trust Anchor Management - Di Ma; Shuo Shen (Dianxin kexue)
RPKI is a PKI designed to support validation of claims by current holders of internet number resources （IPv4 addresses, IPv6 addresses and AS numbers）, which is employed to establish a secure inter-domain routing system. However, the deployment of RPKI has its own risks falling into the category of operations and management. To give countermeasures, local trust anchor management for RPKI was introduced to build RPKI safeguard. A brief introduction to RPKI safeguard based on local trust anchor management was given, its shortcomings were analyzed and hence the potential research points of RPKI safeguard for the coming future were presented.